CULINARY ETHNOLOGY OF PODILLIA: FEATURES AND RECIPE INGREDIENTS - Bazhenova, S.; Khoptiar, A. (Municipal economy of cities. Series: «Economy science», 2023)
The article considers the actual and unique issue of studying the traditional recipes of Podillia to identify their uniqueness and regional features. We determined that this issue’s regional and local lore aspect opens vast opportunities for its use as a historical source. Patterns of the presence or absence of particular themes and motives often find their reasons in historical factors. To some extent, this also applies to such an area as the country’s cuisine and culinary traditions. The study revealed that the functioning of folk customs is subordinated to more practical than aesthetic requests. Where the question of folk traditions, beliefs, customs and rites, life and lifestyle of the population arises, only there is a prerequisite for the appearance of authentic cuisine and original recipes. Thus, the etiology of such folk recipes lags far behind the customs etiology in time. The previous research has proven that the identified features of the development of Ukrainian cuisine relate specifically to the national culinary traditions and customs of the population of Podillia. This layer of folk culture needs urgent exploration. A detailed study of the peculiarities of cuisine and culinary traditions can give ethnographers and culturologists valuable information about our people’s history, ancient traditions, beliefs, and culture. The specificity of the researched object and the degree of study of the chosen topic determined the purpose of the article, which is studying and organising the characteristic features of the culinary heritage of Podillia, as well as collecting and registering authentic recipes and methods of cooking dishes that reflect the cultural heritage of this region of Ukraine. The practical significance of the obtained results is that its main provisions can be used by specialists in various fields: ethnographers, folklorists, culturologists, historians, geographers, and tourism specialists. The personal contribution of the authors consists of the systematisation of folk culinary traditions and folk recipes of Podillia and a comprehensive study of the genealogy of ethnic cuisine.